Oral abrocitinib in the treatment of granuloma annulare: a case report - Wenyan Liu; Weifeng Chen; Xin Tian; Yihui Yu; Junhui Zhu; Jingyao Liang; Xibao Zhang (Journal of Dermatological Treatment)
Aim: To evaluate the therapeutic efficacy and safety of JAK inhibitor abrocitinib in patients with localized granuloma annulare (GA) and to review the available cases documented in English.Methods: We presented a patient who had a persistent, localized granuloma anulare (GA) for one year and did not respond to traditional therapies. This patient was treated with oral abrocitinib at a dosage of 150 mg daily.Results: After 6 weeks of treatment with abrocitinib, the patient exhibited notable symptom improvement with no new lesions. No adverse events or recurrences were reported during the 5-month follow-up period.Conclusions: Abrocitinib may be a promising and safe treatment option for patients with localized GA who do not respond to traditional therapies.